Calculation of Octanol/Water Partition Coefficients of Ferrocene Derivatives - AHMEDI, R.; LANEZ*, T. (Asian Journal of Chemistry, 2009)
Octanol/water partition coefficients, log P, of ferrocene derivatives were determined by theoretical calculations and predictions from literature methods. The calculations were developed on the basis of the adaptation of the existing Rekker approach. The prediction ability of the developed approach was estimated by the comparison of the calculated log P values with the experimental values. Although the log P values determined by the proposed methods are close to the experimental values. The calculated and experimental log Ps of ferrocene derivatives lacking a bulky group are significantly closer than those obtained for ferrocenes containing a bulky group.